2014
DOI: 10.1590/1516-3180.2014.1325737
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between Klinefelter syndrome and diaphragmatic hernia. A case report

Abstract: CONTEXT: Intrathoracic cystic lesions have been diagnosed in a wide variety of age groups, and the increasing use of prenatal imaging studies has allowed detection of these defects even in utero. CASE REPORT: A 17-year-old pregnant woman in her second gestation, at 23 weeks of pregnancy, presented an ultrasound with evidence of a cystic anechoic image in the fetal left hemithorax. A morphological ultrasound examination performed at the hospital found that this cystic image measured 3.7 cm x 2.1 cm x 1.6 cm. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…6 Valdez et al reported a case in which CDH and KS were diagnosed prenatally. 7 In a recent review on CDH by Wynn et al, the cause of approximately 80% of CDH cases was unknown with no genetic abnormalities, demonstrating our limited understanding of the genetic etiologies of CDH as well as suggesting nongenetic, non-Mendelian, or multifactorial etiologies for CDH. 8 In addition to single-gene mutations in GAT4, GATA6, MYH10, ZFPM2/FOG2, and DIPS1, other rare single-gene mutations have also been reported with some patients with CDH.…”
Section: Discussionmentioning
confidence: 99%
“…6 Valdez et al reported a case in which CDH and KS were diagnosed prenatally. 7 In a recent review on CDH by Wynn et al, the cause of approximately 80% of CDH cases was unknown with no genetic abnormalities, demonstrating our limited understanding of the genetic etiologies of CDH as well as suggesting nongenetic, non-Mendelian, or multifactorial etiologies for CDH. 8 In addition to single-gene mutations in GAT4, GATA6, MYH10, ZFPM2/FOG2, and DIPS1, other rare single-gene mutations have also been reported with some patients with CDH.…”
Section: Discussionmentioning
confidence: 99%